المدائح النبوية عند الشاعرين: أحمد شوقي وخليل الله خليلي (دراسة في أوجه التشابه والتباين وإمكانية التأثير والتأثر) - Fakhry, Abdel-Sabour (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
In this article, the researcher discusses the comparison between two renowned poets in the modern Arab literary world, Ahmad Shawqi and Khalilullah Khalili. The researcher provides an overview of Ahmad Shawqi's life translation, literary writings, the key characteristics of his poetry, and its influence in the world of poetry. Additionally, the article delves into the life of the national Afghan poet, Khalilullah Khalili, his writings, the characteristics and purposes of his poetry, while highlighting the similarities between the two poets' personalities. The article explores the central themes around which the poets' works revolve, particularly their sentiments towards the Prophet Muhammad and how they connect this religious occasion to the realities of life. The researcher identifies over ten similarities between the poems of the two poets and also highlights clear differences that exclude the possibility of mutual influence or being influenced, despite their contemporaneity. Finally, the researcher summarizes the most significant findings and comparisons between the two poets in twelve points, evaluating the way they approached their praises of the Prophet in terms of content, emotion, language, and style, while offering some assessments.